Avoiding extremes using partial control. Issue 2 (1st February 2016) - Das, Suddhasattwa; Yorke, James
Abstract : Dynamical systems can be prone to severe fluctuations due to the presence of chaotic dynamics. This paper explains for a toy chaotic economic model how such a system can be regulated by the application of relatively weak control to keep the system confined to a bounded region of the phase space, even in the presence of strong external disturbances. Since the control here is weaker than the disturbance, the system cannot be controlled to a particular trajectory, but under certain circumstances it can be partially controlled to avoid extreme values. Partial control depends on the existence of a certain set called a 'safe sets'. We describe the safe set and how it varies with parameters, sometimes continuously and sometimes discontinuously.